Mitochondrial d-loop variation, coat colour and sex identification of Late Iron Age horses in Switzerland. (April 2016) - Elsner, Julia; Deschler-Erb, Sabine; Stopp, Barbara; Hofreiter, Michael; Schibler, Jörg; Schlumbaum, Angela
Abstract: In the Celtic world, horses enjoyed a prominent position as status symbols and objects of veneration, yet little is known about these Celtic horses except that they were rather small. The Late Iron Age was a time defined by increasing inter-cultural contact between Celtic peoples and the Romans. This is, amongst other features, observable in the phenotypes of domestic livestock such as horses. Amongst the usually small animals, larger ones are rarely but regularly encountered in the archaeological record. We have investigated mitochondrial (mt) DNA d-loop diversity, sex and coat colour using bones from 34 horses of different size from three Swiss sites (Mormont, Basel-Gasfabrik, Aventicum) most of them dating from 150 to 50 BCE. The aim was to characterise the diversity of matrilineages and coat colourations of Iron Age horses, and to identify molecular sex. We detected eleven mt haplotypes clustering into six haplogroups (B, D, F, I, X2, X3) in the ancient dataset (n = 19). Large individuals were all male, but smaller stallions were also identified; molecular sexing confirmed and augmented to morphological results. The horses were bay, chestnut and black in colour, and spottings or dilutions were absent in all animals. With a simplified primer system to detect premature greying, white coats can be excluded as well. The limited colour range proposes selection for monochrome animals. Additionally, ancient matrilineages were compared to modern horses from regions appertaining to the Late Roman Republic and to European pony breeds. Based on Principal Component Analysis (haplotype frequencies) and FST -values (genetic distances) the mtDNA variation of the Iron Age horses investigated here has survived in modern European breeds, particularly in northern European ponies.